Sharing the vision: collective communication within LGBT leadership - Lucio, William (Kansas State University, 2016)
Leadership is a phenomenon studied in all cultures (Murdock, 1967), yet representation in the diversity of influential leaders is often limited (Moon, 1996). In order to understand the full breadth of leadership scholarship, it is essential that research focuses on how leadership is both enacted and communicated in underrepresented groups. A group that is currently facing marginalization from dominant culture is the Lesbian, Gay, Bisexual, and Transgender (LGBT) community. With no national anti-discrimination law in place to protect the individuals belonging to this community (American Civil Liberties Union, 2016) it is vital to understand how leaders within this marginalized group are motivating others to fight to enact change. While influential organizations like The Human Rights Campaign (HRC) are fighting for social justice on a national level, it is important to understand how local organizations are engaging in communicative leadership to motivate others to enact change in their own community. This study seeks to understand how leadership is communicated within a local LGBT rights organization (given the pseudonym the Lesbian Gay Bisexual Transgender Campaign, or LGBTC) and to identify the ways LGBT leaders motivate others to enact social change. Using ethnographic methodology, the researcher observed four monthly board meetings held by this group (lasting approximately an hour and a half each) and conducted a focus-group interview where the participants confirmed observations and answered follow-up questions from the ethnographic observations. A qualitative thematic analysis revealed two common themes: the first theme, cohesive communication, was exemplified through organizational procedures that allowed for collective discussion and expression of individuality by emphasizing and depending on group members’ personal expertise. The second theme, proactive communication, emerged through group members’ communication to evoke tenacious defense strategies to counter the opposition and engage in outreach with external organizations. These leadership communication behaviors resulted in two critical implications on the theoretical and practical levels. In regards to the theoretical implications, LGBT leaders, who have been typically characterized as predominantly transformational, were found to enact leadership outside of that typology, actually engaging in relational styles through shared leadership, communicating in a way that relies on interaction and emotional expression. On a practical level, other marginalized groups could benefit from inclusivity, or the mode of collective leadership this particular LGBT Rights Group engaged in. By including multiple voices and having a variety of minority representation, the LGBTC was able to successfully motivate community change. Other marginalized groups experiencing social injustice may be able to motivate others to enact change by adopting this mode of collective communication through shared leadership.
Keywords: Leadership communication; Lesbian Gay Bisexual Transgender (LGBT) leadership; Marginalized leadership; Shared leadership; Social change